ANALISIS INOVASI PELAYANAN PUBLIK PADA ADMINISTRASI KEPENDUDUKAN MELALUI KADOKU SEHATI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMBAWA BARAT - KARTAPATI, KARTAPATI; UMAR, UMAR; KHADAFIE, MUAMMAR (GANEC SWARA, 2023)
In the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 30 of 2014 concerning Guidelines for Public Service Innovation it is stated that: "Public Service Innovation is a breakthrough type of service which is either an original creative idea/idea and/or an adaptation/modification that provides benefits to society , either directly or indirectly.” As an effort to realize quality public services, it is based on the Decree of the Head of the West Sumbawa Regency Population and Civil Registration Service. No. 067/019/DISDUKCAPIL/2021 Concerning the Formation of the Sumbawa Regency Kadoku Sehati Service Innovation Implementation Team, the aim is to simplify population administration matters for newlyweds. The research method used is a qualitative research method. The population and sample in the research were government officials tasked with carrying out Kadoku Sehati population administration services and the people of West Sumbawa district who were involved in implementing these activities. From the research results, it is known that the Kadoku Sehati population administration public service innovation in West Sumbawa Regency has been implemented very well, because it has fulfilled the rules of public service innovation and also won second best in the West Sumbawa Regency innovation competition